1999
DOI: 10.1177/104225879902400203
|View full text |Cite
|
Sign up to set email alerts
|

Loosely Coupled Systems for Corporate Entrepreneurship : Imagining and Managing the Innovation Project/Host Organization Interface

Abstract: This paper explores the concept of loosely coupled systems as an Image representing the Interface between Innovation projects (emerging organizations) and their hostcorporations (existing organizations). The model calls attention to waysIn which management's actions create moreor less Independence between Innovation and hostorganization systems. Analyzing Interviews from 13 Innovation projects In two Fortune 500 corporations, everyday actions that loosen and couple Innovation and management systems are Identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 19 publications
(19 reference statements)
1
30
0
1
Order By: Relevance
“…Although some employees may have a natural will to act entrepreneurially, we do believe that part of the autonomous behavior is stimulated by managers' attitudes. This has support from Burgelman's (1983b) approach, suggesting that middle management play a crucial role in supporting autonomous initiatives from employees, which is confirmed by Heller's (1999) studies on innovative projects in existing corporations. According to Heller (1999), the capacity to create an independent organizational structure for entrepreneurial initiatives relies much more on management's actions than organizational systems.…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…Although some employees may have a natural will to act entrepreneurially, we do believe that part of the autonomous behavior is stimulated by managers' attitudes. This has support from Burgelman's (1983b) approach, suggesting that middle management play a crucial role in supporting autonomous initiatives from employees, which is confirmed by Heller's (1999) studies on innovative projects in existing corporations. According to Heller (1999), the capacity to create an independent organizational structure for entrepreneurial initiatives relies much more on management's actions than organizational systems.…”
Section: Introductionsupporting
confidence: 56%
“…Burgelman and Sayles (1986) observed that Corporate Entrepreneurship (CE) may be formal or informal. In formal CE, or induced behavior (Ferreira, 2001;Heller, 1999), the organization tries to facilitate, in every way, the generation of entrepreneurs and their initiatives. To a greater or lesser extent, these businesses:…”
Section: Induced or Autonomous Entrepreneurial Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…These research efforts suggest that CE is pervasive and multi-faceted. In the same vain, Heller (1999) has focused on CE and the innovation process of a firm.…”
mentioning
confidence: 99%